Pachylarnax praecalva Dandy (Magnoliaceae): a new record for Thailand - Sawangchote, P.; Sirirugsa, P.; Leerativong, J.; Sridith, K.; Saknimit, T.; Eksomtramage, L.; Jornead, S. (Thai Forest Bulletin (Botany), 2014)
A newly recorded species for Thailand, Pachylarnax praecalva Dandy. was found on a ridge in Ton Nga Chang Wildlife Sanctuary. Nakhon Si Thammarat at ca. 550 m altitude. The species is described and illustrated.